Pengaruh Aksesibilitas Laporan Keuangan dan Sistem Akuntansi Keuangan Daerah terhadap Good Governance yang Dimediasi oleh Akuntabilitas Pengelolaan Keuangan Daerah (Studi Empiris pada Satuan Kerja Perangkat Daerah Kota Bogor) - Diki Susanto; Bambang Pamungkas; David H.M. Hasibuan (PT. PENERBIT TIGA MUTIARA, 2024)
This study aims to analyze the role of regional financial management accountability as a mediator between the accessibility of regional financial reports and regional financial accounting systems in relation to good governance in the Regional Apparatus Organizations of Bogor City. Utilizing a quantitative approach, this study employs Structural Equation Modeling (SEM) with the assistance of PLS and IBM Statistics SPSS 26.0 programs for data analysis. The research sample consists of 108 respondents who are employees meeting specific criteria within the Regional Apparatus Organizations of Bogor City. Data collection was conducted through questionnaire distribution to these respondents. The analysis results indicate that regional financial management accountability plays a significant role in mediating the relationship between the accessibility of regional financial reports and regional financial accounting systems towards good governance. These findings suggest that improving the accessibility of financial reports and enhancing regional financial accounting systems can promote the establishment of good governance through increased accountability in financial management. This research provides an important contribution to understanding the factors influencing the realization of good governance at the regional government level and can serve as a reference for policymakers in formulating strategies to improve the quality of governance, particularly in aspects of regional financial management in Bogor City and other regions in Indonesia.